NIKEL ATOMLARINI KIRITISH ORQALI POLIKRISTALL KREMNIYNING ELEKTR-FIZIK XUSUSIYATLARINI YAXSHILASH - Ismaylov, Q.A.; Ollamberganov, Sh.Z. (SCIENCE and SOCIETY, 2025)
The aim of this work is to determine and analyze the mechanisms of the influence of nickel atoms on the properties of polysilicon. 1000 nickel atoms were deposited on polycrystalline silicon and the composition of nickel clusters was studied using scanning electron microscopes. The effect of adding nickel to polycrystalline silicon on the electrophysical parameters was studied, the size and composition of nickel atom clusters were studied. The electrophysical parameters of samples without nickel atoms and doped with nickel atoms were determined by the C-V method. measured and compared. The results showed that the introduction of nickel helps to improve the quality of polycrystalline silicon material.
Keywords: polycrystal; nickel; diffusion; cluster; silicon; impurity atom